Effectiveness of dual-wavelength (Diodes 980 Nm and 635 Nm) laser approach as a non-surgical modality in the management of periodontally diseased root surface: a pilot study - Nicola De Angelis; Reem Hanna; Antonio Signore; Andrea Amaroli; Stefano Benedicenti (Biotechnology & Biotechnological Equipment, 2018)
Conventional periodontal therapies have been widely discussed in the literature. The results of these therapies, surgically and non-surgically, have demonstrated high predictability and stable maintenance over time. With some clinical indications, such as inflamed sites with consistent bleeding on probing (BOP), it can be challenging for the root planning procedure to achieve predictable outcomes. Therefore, the aim and objectives of the present study were to evaluate whether the dual-wavelength (980 and 635 nm) laser therapy at lower power settings can be beneficial as a combined non-invasive modality in the management of periodontally diseased root surface in terms of improving the periodontal parameters. Thirty-five healthy patients were enrolled in this study. All patients had at least one pocket in the anterior and posterior teeth with initial periodontal pocket depth (PPD) > 6 mm associated with evidence of clinical inflammation, i.e. bleeding on probing (BOP++ or BOP+++) with no gingival recession. The treatment protocol utilized combined therapy of conventional debridement immediately followed by application of dual-wavelength laser therapy (photo-ablation and photodynamic therapies) at lower power settings. The results showed that all the pockets of involved teeth had an average gain of 3 mm of the clinical attachment level with no sign of BOP and reduction in the mobility of the teeth 35 days post-operatively. Thus, the utilization of the dual-wavelength approach of laser-assisted therapy at lower power settings appears to provide a promising and predictable non-invasive clinical approach in the management of compromised periodontally involved teeth.